SERAT ECENG GONDOK SEBAGAI BAHAN ALTERNATIF ADMIXTURE PADA LASTON TIPE XI SNI 03-1737-1989 DITINJAU TERHADAP NILAI-NILAI UJI MARSHALL - Errine Yulia Rizqi Intanti; Zulkifli Lubis (Litbang Pemas - Universitas Islam Lamongan, 2018)
In Indonesia, the road construction has experienced a fairly good development. From a wide range of road constructions, flexible pavement is the most chosen one because its characteristics: easy, fast, and efficient. However, flexible pavement has many weaknesses, for example the premature damage on the road surface after some time passed by the traffic so that the road cannot reach the planned age. For that, it is done a research to add a hot asphalt mixture material that aims to improve the quality of the mixture results. The selected ingredient is natural water hyacinth. The method used is trial and error with reference of SNI 03-1737-1989. Variations used are 2%, 4%, 6%, 8% and 10% of the asphalt weight, asphalt level used is 5.72 %. Of the 5 variations of mixture used on Type XI Asphalt Concrete Layer, it is obtained the result that the water hyacinth fiber level which has the best score and meet the specifications of SNI 03-1737-1989 is on the percentage of 6% which obtained from calculation data using graphs and regression model where Marshall Stability is equal to 644,46 Kg, flow 3,39 mm, VMA (voids in the mineral aggregate) is equal to 13,83 %, VFWA (voids filled with asphalt) is equal to 65,35%, VIM (voids in the mix) is equal to 2,52 %, density of 2.31 gr/cc, and Marshall Quotient of 164.03 Kg / mm.